2018
DOI: 10.1186/s13041-017-0345-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of the neuro-glio-vascular machinery in the adult brain

Abstract: The adult brain actively controls its metabolic homeostasis via the circulatory system at the blood brain barrier interface. The mechanisms underlying the functional coupling from neuron to vessel remain poorly understood. Here, we established a novel method to genetically isolate the individual components of this coupling machinery using a combination of viral vectors. We first discovered a surprising non-uniformity of the glio-vascular structure in different brain regions. We carried out a viral injection sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Likewise, both astrocytes and RGL cells of the dentate gyrus contact the vasculature via their fine processes [ 41, 42 ]. The functional significance of these vascular contacts remains uncertain, but those of RGL cells seem to guide fate specification and proliferation of progenitor cells via hematogenously-derived cues, while those of astrocytes may link hippocampal glucose metabolism to glutamatergic synaptic transmission at the doublecortin (DCX) stage [ 39, 43, 44 ].…”
Section: The Anatomical Formation Of Hippocampal Vasculature Neuronsmentioning
confidence: 99%
“…Likewise, both astrocytes and RGL cells of the dentate gyrus contact the vasculature via their fine processes [ 41, 42 ]. The functional significance of these vascular contacts remains uncertain, but those of RGL cells seem to guide fate specification and proliferation of progenitor cells via hematogenously-derived cues, while those of astrocytes may link hippocampal glucose metabolism to glutamatergic synaptic transmission at the doublecortin (DCX) stage [ 39, 43, 44 ].…”
Section: The Anatomical Formation Of Hippocampal Vasculature Neuronsmentioning
confidence: 99%
“…We should note that in using the CAV method that we recently reported to target astrocytes, we found severe defects in hippocampusdependent memory following diphtheria toxin mediatedablation of astrocytes 8 . This provides us a novel noninvasive option to target astrocytes for behavior studies.…”
Section: Genetic Manipulationsmentioning
confidence: 99%
“…Recently, we reported that intravenously delivered Canine Adenovirus 2 (CAV2) preferentially targets perivascular astrocytes throughout the adult brain 8 . We can therefore deliver transgenes to astrocytes systemically, rather to only regions closely surrounding our injection site.…”
Section: Canine Adenoviral Astrocyte Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] ECs are vital bioactive and endocrine organs with critical functions in controlling vascular metabolism. [2] ECs situated between vascular tissues and blood can not only accomplish the metabolism of interstitial fluid and blood but also synthesize and secrete many vasoactive substances that maintain normal blood flow and long-term vessel patency as well as regulate blood pressure and anticoagulation-coagulation balance. [3]…”
Section: Introductionmentioning
confidence: 99%